3D FE modelling and validation of frictional contact with partial slip in compression–shift–rolling evolution. Issue 1 (2nd January 2016) - Wei, Zilong; Li, Zili; Qian, Zhiwei; Chen, Rong; Dollevoet, Rolf
Abstract: This paper presents a three-dimensional finite element approach capable of realistically simulating a wide range of contact types with partial slip. The approach is demonstrated by analysing the evolution of instationary contact from compression to shift till stationary rolling. It is systematically validated using classical solutions, i.e. Hertz theory for the frictionless normal problem, and Spence solution for frictional compression, Cattaneo solution for tangential shift and Kalker's CONTACT for frictional rolling. The effect of plastic deformation on the distributions of pressure, adhesion–slip regions, surface shear traction and micro-slip is investigated. It is shown that plastic deformation makes the normal contact solution dependent on the tangential contact solution. Plastic deformation partly damps out the structure vibrations and significantly diminishes the magnitude of micro-slip. The presented model can be extended to simulate the start-off and braking of railway vehicles, to optimize the traction and braking control systems of trains, as well as to reduce the related damages.